Evaluation of a new rapid anti‐HbF FITC assay, Trillium QuikQuant, for detection and quantitation of foetomaternal haemorrhage. Issue 1 (14th August 2012) - Fong, E. A.; Finlayson, J.; Robins, F.; Davies, J.; Joseph, J.; Rossi, E.; Grey, D. E.
Summary: Introduction: This study evaluated a new product for flow cytometric foetomaternal haemorrhage (FMH) quantitation, Trillium QuikQuant anti‐HbF FITC kit (Trillium Diagnostics, USA), in comparison with the Millipore anti‐HbF FITC method. Methods: Blood from 67 antenatal or postpartum RhD‐negative women together with 108 samples spiked with 0.2%, 0.4%, 0.6%, 2%, 4%, 5%, 6%, 8% and 10% of foetal red cells were analysed by both methods. Results: Results for both methods were linear to 10% foetal red cells. Analysis using the Wilcoxon test found that there was no difference between the paired results of Trillium QuikQuant and the expected values of the spiked samples ( P = 0.48). In contrast, Millipore anti‐HbF FITC gave statistically higher results compared with both the expected values and Trillium QuikQuant anti‐HbF FITC ( P = 0.0003 and P < 0.0001, respectively). The Bland–Altman plot for Trillium QuikQuant showed a mean difference of only 0.06% below the expected values, whilst Millipore was 0.13% above. The analysis time with Trillium QuikQuant was approximately 40 min, requiring significantly less hands‐on time than the Millipore method that required an additional four wash steps. Conclusion: Trillium QuikQuant is a new precise, accurate and rapid flow cytometric kit method for the quantitation of FMH in both the antenatal and postpartum period.